A human‐computer interaction principles based framework to assess the user perception of web based virtual research environments - Keraminiyage, Kaushal; Amaratunga, Dilanthi; Haigh, Richard (International Journal of Strategic Property Management, 2009)
Due to various challenges and opportunities such as globalisation of research agenda and advancements in information and communication technologies, research collaborations (both international and national) have become popular during the last decade more than ever before. Within this context, the concept of Virtual Research Environments(VRE) is an emerging concept looking at addressing the complex challenges associated with conducting collaborative research. Even though concept of VRE is at its infancy, it is important to assess user perception about those, both to establish its success of uptake and future development strategies. However, to date, there is no formal method established to evaluate VREs. This paper reports a strategy adopted within an international collaborative research project (EURASIA) to evaluate its custom built VRE, VEBER, using the well known Computer Human Interaction principles.First Publish Online: 18 Oct 2010